Differences in reimbursement listing of anticancer therapies in China: an observational study - Guan, Xiaodong (BMJ Open, 2020)
OBJECTIVE: Access to highly priced anticancer medications usually requires insurance coverage. A first step towards coverage of such medications is their inclusion in reimbursement lists. We assessed listing for reimbursement in China between 2009 and 2018 of anticancer medications on the WHO’s Essential Medicines List. SETTING AND STUDY DESIGN: Using publicly available data, we assessed which anticancer medications listed in the 20th WHO Model List of Essential Medicines (EML) were included in China’s National Reimbursement Drug List (NRDL). For five targeted anticancer medications on the WHO EML, we also assessed inclusion in the 31 Chinese Provincial Reimbursement Drug Lists (PRDLs). Logistic regression was used to test whether inclusion of targeted anticancer medications was associated with provincial economic levels. PRIMARY OUTCOME MEASURES: Inclusion of five targeted anticancer medications in the NRDL and PRDLs before and after 2017. RESULTS: The 2017 NRDL included all anticancer medications on the WHO EML (except for one not approved in China at the time), and by 2018, all 31 PRDLs listed the targeted anticancer medications except for nilotinib; four provinces had covered all five targeted medications before the 2017 NRDL coverage mandate. Provincial economic level and regional incidence of specific cancers seemed unrelated to the inclusion of five targeted anticancer medications in PRDLs. CONCLUSION: Our findings suggest that by including medications in the national and provincial reimbursement lists, China has taken an important first step in promoting access to targeted anticancer medications. Further research is needed to determine whether inclusion in PRDLs improved the availability, appropriate use and affordability of highly priced targeted anticancer medications in China.